Mining WC-Co hard alloy and preparation method thereof

By adding medium-grain tungsten carbide, NbScN and NbC to the mining cemented carbide and optimizing the grain ratio of WC, the problem that it is difficult for cemented carbide to achieve high toughness and high wear resistance at the same time under harsh working conditions is solved. , significantly improves its comprehensive performance and service life.

CN119392079AActive Publication Date: 2025-02-07HUBEI MILALION METALLURGICAL MACHINERY CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411571613.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

It is difficult for existing mineral cemented carbides to achieve high toughness and wear resistance at the same time under harsh working conditions, resulting in insufficient service life.

Method used

By adding medium-grain tungsten carbide, NbScN and NbC, the ratio of ultracoarse grain WC to medium-grain WC is optimized, the hardness and wear resistance of the bonded phase are enhanced, and the uniform dispersion of NbScN and NbC is improved through surface modification. sex.

Benefits of technology

It significantly improves the fracture toughness, wear resistance and fatigue resistance of cemented carbide, extends the service life, and improves the overall strength and bending resistance of the alloy.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of hard alloy, and particularly discloses a mining WC-Co hard alloy and a preparation method thereof. The mining WC-Co hard alloy comprises, by mass, 15%-30% of Co, 0%-1.5% of NbScN, 0%-1.5% of NbC and the balance hard phase WC. The hard phase WC comprises ultra-coarse grain WC with the average grain size ranging from 6.0 micrometers to 9.0 micrometers and medium grain WC with the average grain size ranging from 1.0 micrometers to 3.0 micrometers. The mining WC-Co hard alloy has the advantages of being good in comprehensive performance, high in hardness and good in toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cemented carbide, and more specifically, to a WC-Co cemented carbide for mining and a preparation method thereof. Background Art

[0002] With its excellent comprehensive performance, cemented carbide is widely used in cutting, infrastructure, mining, molds and wear-resistant parts. Among them, mining cemented carbide used for mining is a very important component. Mining cemented carbide products should have the high hardness required to resist wear and the high toughness required to resist impact fracture. As the use environment of mining cemented carbide becomes more and more harsh and the working conditions become more and more complex, higher requirements are placed on the comprehensive performance of mining cemented carbide. How to achieve high toughness and high wear resistance as much as possible to increase the service life of cemented carbide has always been the goal and direction of cemented carbide research.

[0003] Ultra-coarse grained tungsten carbide exhibits excellent wear resistance and thermal fatigue resistance. However, as the size of tungsten carbide particles in cemented carbide increases, the size of the bonding phase also increases. The hardness of the bonding phase is much lower than that of tungsten carbide. The bonding phase will be worn to a limited extent during the service of the cemented carbide. Therefore, the performance of the bonding phase will greatly affect the life of the cemented carbide. How to strengthen the bonding phase to improve the wear resistance and toughness of ultra-coarse cemented carbide is a problem that needs to be solved urgently. Summary of the invention

[0004] In order to obtain a cemented carbide product with high hardness and high toughness, the present application provides a WC-Co cemented carbide for mining and a preparation method thereof.

[0005] In the first aspect, the present application provides a WC-Co cemented carbide for mining, which adopts the following technical solution:

[0006] A WC-Co hard alloy for mining, comprising Co in a mass ratio of 15-30%, NbScN in a mass ratio of 0-1.5%, NbC in a mass ratio of 0-1.5%, and the balance being a hard phase WC;

[0007] The hard phase WC includes ultra-coarse grain WC with an average grain size of 6.0-9.0 μm and medium grain WC with an average grain size of 1.0-3.0 μm.

[0008] By adopting the above technical solution, by adding medium-grained tungsten carbide, the medium-grained tungsten carbide can be filled into the larger pores of the ultra-coarse-grained tungsten carbide, greatly reducing the gaps between the tungsten carbide particles, forming a more compact particle arrangement; the medium-grained WC can be partially dissolved in the liquid Co, which plays a role in strengthening the Co bonding phase, improving the hardness, wear resistance and service life of the bonding phase; at the same time, by optimizing the ratio of ultra-coarse-grained WC to medium-grained WC, the cemented carbide is more superior in terms of fracture toughness, wear resistance and fatigue resistance.

[0009] As an inhibitor, NbC can be dissolved in the binder phase to produce solid solution strengthening or dispersion strengthening, inhibit the excessive growth of WC grains, and when the cemented carbide is subjected to external force, it can play a pinning role on the dislocation movement in the binder phase, thereby improving the overall strength of the cemented carbide and significantly improving the comprehensive performance of the cemented carbide; at the same time, NbC can promote the solid solution or dispersion of NbScN in the binder phase, and the Sc and N elements in NbScN can refine the grains, reduce the grain boundaries, improve the lattice distortion, and improve the toughness and bending resistance of the cemented carbide. Sc can also further enhance the hardness and wear resistance of the cemented carbide. Therefore, when NbC and NbScN are added together, the hardness, wear resistance, toughness and bending resistance can be obtained. Further, the inventors found that the strength of the alloy was unexpectedly improved by the addition of mesogenic grains and the addition of NbScN and NbC, which may be due to the fact that the mesogenic grains, NbScN and NbC enhance the strengthening effect of the binder phase through the above-mentioned different mechanisms, thereby improving the hardness of the alloy.

[0010] Preferably, the cemented carbide comprises 0.5-1.0% NbScN and 0.5-1.0% NbC in a mass ratio.

[0011] Preferably, the cemented carbide comprises 0.6% NbScN and 0.8% NbC in a mass ratio.

[0012] By adopting the above technical solution, NbC and NbScN cooperate with each other, have a better solid solution strengthening effect on the Co bonding phase, significantly improve the mechanical properties of the cemented carbide, and improve the bending strength and fracture toughness. To a certain extent, it can improve the wettability of the WC grains and the bonding phase, inhibit the excessive growth of the grains, and at the same time improve the corrosion resistance and oxidation resistance of the bonding phase to a certain extent; when 0.6% NbScN and 0.8% NbC are used, the alloy performance is optimal, which may be due to the fact that at the above ratio, the solid solution or dispersion effect of the two in the bonding phase is the best, and the improvement of the alloy performance is the greatest.

[0013] In the second aspect, the present application provides a method for preparing WC-Co cemented carbide for mining, which adopts the following technical solution:

[0014] A method for preparing WC-Co cemented carbide for mining comprises the following steps:

[0015] According to the proportion, ultra-coarse particle WC powder and Co powder are mixed and prepared, and then 1.5-2.5% of the total weight of the ingredients is added to the molding agent, mixed and wet-milled for 14-20 hours, and then spray-dried and granulated to obtain an ultra-coarse particle mixture; the ultra-coarse particle WC powder has a Fess particle size of 13-20 μm;

[0016] According to the proportion, medium-grained WC powder, Co powder, NbScN alloy powder and NbC alloy powder are mixed and prepared, and then a molding agent of 1.5-2.5% of the total weight of the ingredients is added, mixed and wet-milled for 20-30 hours, and then granulated by spray drying to obtain a medium-grained mixture; the Fess particle size of the medium-grained WC powder is 2-8 μm;

[0017] The ultra-coarse particle mixture and the medium particle mixture are mixed and batched at a mass ratio of (85:15)-(95:5) for 40-80 minutes, pressed into shape, vacuum sintered to remove the molding agent, and then low-pressure hot isostatic pressing sintered at 1420-1450°C to obtain WC-Co cemented carbide for mining.

[0018] By adopting the above technical solution, the ultra-coarse particle mixture and the medium particle mixture are separately batched, wet-milled, dried and granulated, and then mixed and sintered, which helps to ensure the stability of the alloy structure during the sintering process, and can ensure the stability of the ratio of ultra-coarse grain WC and medium grain WC, avoiding the occurrence of grain size homogenization.

[0019] By mixing and batching, the ultra-coarse particle mixture and the medium particle mixture are evenly mixed, and the medium particle mixture is dispersed between the ultra-coarse particle mixture, which reduces the possibility of the ultra-coarse particles being adjacent to each other and sintered to form polycrystals during pressing, makes the particle arrangement more dense, and reduces the gaps between WC particles;

[0020] During sintering, the smaller particles in the medium-grained WC dissolve into the liquid binder phase to strengthen the binder phase. The interface segregation and solid solution strengthening of NbScN and NbC further strengthen the binder phase, improve the wear resistance and toughness of the cemented carbide, inhibit the excessive increase of grains, and improve the wettability between the binder phase and the hard phase. The binder phase surrounds the ultra-coarse grained WC, further promoting sintering densification and improving the hardness of the cemented carbide. Mixing the medium-grained WC powder with the NbScN alloy powder and the NbC alloy powder is beneficial to jointly achieve the strengthening effect on the binder phase and improve the alloy strength under the surrounding distribution effect.

[0021] Preferably, the combined mass ratio of the ultra-coarse particle mixture to the medium particle mixture is 9:1.

[0022] By adopting the above technical solution, the ratio of ultra-coarse-grained WC and medium-grained WC is crucial to the fracture toughness, wear resistance, fatigue resistance and other properties of cemented carbide. The inventors found through experiments that when the batch mass ratio is 9:1, cemented carbide can achieve the best comprehensive performance.

[0023] Preferably, the molding agent is polyethylene glycol.

[0024] Preferably, the NbScN alloy powder and the NbC alloy powder need to be surface-modified by an alcoholamine compound, and the surface modification method is: NbScN powder and / or NbC powder, anhydrous ethanol, and diethanolamine are mixed in a mass ratio of 1: (0.1-0.2): (0.001-0.005), ball-milled for 2-6 hours, and vacuum-dried.

[0025] By adopting the above technical scheme, the amount of NbScN alloy powder and NbC alloy powder added to the cemented carbide is small, and it is easy to disperse unevenly; by surface modification of NbScN alloy powder and NbC alloy powder, while refining the particle size of NbScN alloy powder and NbC alloy powder, diethanolamine is coated on the surface of NbScN alloy powder and NbC alloy powder, thereby improving the compatibility, wettability and dispersion effect of NbScN alloy powder and NbC alloy powder with polyethylene glycol forming agent, improving the dispersion uniformity of NbScN alloy powder and NbC alloy powder, and helping to further improve the comprehensive performance of cemented carbide.

[0026] Preferably, in the step of preparing the ultra-coarse particle mixture, the wet grinding medium is anhydrous ethanol, the liquid-solid ratio is 180-230 ml / kg, and the ball-to-material ratio of wet grinding is 3:1-4:1.

[0027] Preferably, in the step of preparing the medium-particle mixture, the wet grinding medium is anhydrous ethanol, the liquid-solid ratio is 200-300 ml / kg, and the ball-to-material ratio of wet grinding is 3.5:1-4.5:1.

[0028] By adopting the above technical solution and controlling the wet grinding parameters of each step, the ingredients can be evenly mixed to ensure that the mixture has a better tap density.

[0029] Preferably, the batching step is carried out in a double cone mixer or a Y-type mixer.

[0030] Preferably, the pressing step is performed by compression molding.

[0031] In summary, this application has the following beneficial effects:

[0032] 1. Since the present application forms a more compact particle arrangement by adding medium-grained tungsten carbide; the medium-grained WC can be partially dissolved in liquid Co, which plays a role in strengthening the Co bonding phase, improving the hardness, wear resistance and service life of the bonding phase; at the same time, by optimizing the ratio of ultra-coarse-grained WC and medium-grained WC, the cemented carbide is more superior in fracture toughness, wear resistance and fatigue resistance.

[0033] 2. In the present application, NbC and NbScN cooperate with each other to have a better solid solution strengthening effect on the Co bonding phase, significantly improving the mechanical properties of the cemented carbide, and both the bending strength and the fracture toughness are improved. To a certain extent, they can improve the wettability of the WC grains and the bonding phase, inhibit the excessive growth of the grains, and improve the corrosion resistance and oxidation resistance of the bonding phase to a certain extent; at the same time, combined with the grading of the medium grains, the hardness of the alloy is jointly improved. DETAILED DESCRIPTION

[0034] To further help understand the technical solution of the present invention, the technical solution of the present invention is described in more detail below by providing several specific implementation examples. All of these described embodiments are only partial embodiments of the present invention, not all of them.

[0035] The following specific embodiments may be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments; and the reaction devices, monomer compounds, etc. involved in the following embodiments are all commercially available.

[0036] The following specific embodiments may be combined with each other, and the same or similar concepts or processes therein may not be described in detail in some embodiments.

[0037] The following examples are further explanations of the present invention, but the present invention is not limited thereto. Unless otherwise specified in the examples, the percentages are all by mass.

[0038] Example

[0039] Example 1

[0040] This embodiment discloses a WC-Co cemented carbide for mining, and its preparation method is as follows:

[0041] Ultra-coarse particle WC powder and Co powder are mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol is added to the total mass of the ingredients, and wet ball milling is performed in a rolling ball mill. The ball milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients is 200 ml / kg, and the ball-to-material ratio of ball milling is 3.5:1; after ball milling for 18 hours, spray drying and granulation are performed to obtain an ultra-coarse particle mixture;

[0042] The medium-grained WC powder and the Co powder are mixed in a mass ratio of 0.72:0.28, and then 2wt% of the total weight of the ingredients is added with polyethylene glycol, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to the solid ingredients is 260ml / Kg, and the ball-to-material ratio of the ball milling is 4:1. After ball milling for 28h, the mixture is spray-dried and granulated to obtain a medium-grained mixture.

[0043] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0044] In this embodiment, the Fess particle size of the super coarse WC powder is 15 μm, and the carbon content is 6.145 wt %; the Fess particle size of the medium WC powder is 5.0 μm, and the carbon content is 6.15 wt %. The polyethylene glycol is PEG4000.

[0045] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.8 μm, the average grain size of the super-coarse-grained WC was 6.5 μm, the bending strength was 2600 MPa, and the Rockwell hardness HRA was 86.8.

[0046] Example 2

[0047] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0048] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and PEG4000 with a total mass of 2 wt% was added, and wet ball milling was performed in a rolling ball mill, the ball milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; after ball milling for 18 hours, spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0049] Medium-grained WC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% and Co powder were mixed in a mass ratio of 0.72:0.28, and PEG4000 of 2 wt% of the total weight of the ingredients was added, and wet-milled in a rolling ball mill. The milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 260 ml / Kg, and the ball-to-material ratio of ball milling was 4:1. After ball milling for 28 hours, spray drying and granulation were performed to obtain a medium-grained mixture.

[0050] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 8.5:1.5 for 80 minutes, and then molded at 120MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0051] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 2.0 μm, the average grain size of the super-coarse-grained WC was 6.9 μm, the bending strength was 2520 MPa, and the Rockwell hardness HRA was 87.5.

[0052] Example 3

[0053] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0054] Ultra-coarse particle WC powder with Fess particle size of 15 μm and carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and PEG4000 with a total mass of 2 wt% was added, and wet ball milling was performed in a rolling ball mill, the ball milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0055] Medium-grained WC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% and Co powder were mixed in a mass ratio of 0.72:0.28, and PEG4000 of 2 wt% of the total weight of the ingredients was added, and wet-milled in a rolling ball mill. The milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 260 ml / Kg, and the ball-to-material ratio of ball milling was 4:1. After ball milling for 28 hours, spray drying and granulation were performed to obtain a medium-grained mixture.

[0056] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9.5:0.5 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0057] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.6 μm, the average grain size of the super-coarse-grained WC was 6.4 μm, the bending strength was 2740 MPa, and the Rockwell hardness HRA was 85.1.

[0058] Example 4

[0059] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0060] Ultra-coarse particle WC powder with a Fess particle size of 18.5 μm and a carbon content of 6.15 wt% and Co powder were mixed in a mass ratio of 0.7:0.3, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients. The mixture was wet-milled in a rolling ball mill. The milling medium was anhydrous ethanol. The liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of the ball milling was 3.5:1. The mixture was milled for 14 hours, and spray-dried and granulated to obtain an ultra-coarse particle mixture.

[0061] Medium-grained WC powder with a Fess particle size of 8.0 μm and a carbon content of 6.15 wt% and Co powder were mixed in a mass ratio of 0.7:0.3, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients. The mixture was wet-milled in a rolling ball mill. The milling medium was anhydrous ethanol. The liquid-solid ratio of anhydrous ethanol to solid ingredients was 260 ml / kg. The ball-to-material ratio of the ball milling was 4:1. The mixture was milled for 20 hours and spray-dried to obtain a medium-grained mixture.

[0062] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0063] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 3.0 μm, the average grain size of the super-coarse-grained WC was 8.6 μm, the bending strength was 2550 MPa, and the Rockwell hardness HRA was 86.7.

[0064] Example 5

[0065] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0066] Ultra-coarse particle WC powder with a Fess particle size of 14 μm and a carbon content of 6.15 wt% and Co powder were mixed in a mass ratio of 0.85:0.15, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients. The mixture was wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of the ball milling was 3.5:1. The mixture was milled for 20 hours, and spray-dried and granulated to obtain an ultra-coarse particle mixture.

[0067] Medium-grained WC powder with a Fess particle size of 1.2 μm and a carbon content of 6.14 wt% and Co powder were mixed in a mass ratio of 0.85:0.15, and polyethylene glycol was added in an amount of 2 wt% of the total weight of the ingredients, and the mixture was wet-milled in a rolling ball mill. The milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 260 ml / kg, the ball-to-material ratio of the milling was 4:1, the milling was carried out for 30 hours, and the mixture was spray-dried and granulated to obtain a medium-grained mixture.

[0068] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0069] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.2 μm, the average grain size of the super-coarse-grained WC was 6.2 μm, the bending strength was 2580 MPa, and the Rockwell hardness HRA was 86.5.

[0070] Example 6

[0071] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0072] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0073] Medium-grained WC powder, Co powder, NbScN powder and NbC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% are mixed in a mass ratio of 0.7:0.28:0.01:0.01, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg, the ball-to-material ratio of the milling is 4:1, the milling is carried out for 28 hours, and the mixture is spray-dried and granulated to obtain a medium-grained mixture.

[0074] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0075] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.8 μm, the average grain size of the super-coarse-grained WC was 6.4 μm, the bending strength was 2620 MPa, and the Rockwell hardness HRA was 86.8.

[0076] Example 7

[0077] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0078] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0079] Medium-grained WC powder, Co powder, NbScN powder and NbC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% are mixed in a mass ratio of 0.62:0.28:0.05:0.05, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg, the ball-to-material ratio of the milling is 4:1, the milling is carried out for 28 hours, and the mixture is spray-dried and granulated to obtain a medium-grained mixture.

[0080] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0081] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.6 μm, the average grain size of the super-coarse-grained WC was 6.5 μm, the bending strength was 2650 MPa, and the Rockwell hardness HRA was 87.0.

[0082] Example 8

[0083] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0084] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0085] Medium-grained WC powder, Co powder, NbScN powder and NbC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% are mixed in a mass ratio of 0.58:0.28:0.06:0.08, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, and the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg. The ball-to-material ratio of the ball milling is 4:1. The mixture is milled for 28 hours, and spray-dried and granulated to obtain a medium-grained mixture.

[0086] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0087] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.6 μm, the average grain size of the super-coarse-grained WC was 6.4 μm, the bending strength was 2690 MPa, and the Rockwell hardness HRA was 87.2.

[0088] Example 9

[0089] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0090] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0091] Medium-grained WC powder, Co powder, NbScN powder and NbC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% are mixed in a mass ratio of 0.56:0.28:0.08:0.08, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, and the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg. The ball-to-material ratio of the ball milling is 4:1. The mixture is milled for 28 hours, and spray-dried and granulated to obtain a medium-grained mixture.

[0092] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0093] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.6 μm, the average grain size of the super-coarse-grained WC was 6.6 μm, the bending strength was 2670 MPa, and the Rockwell hardness HRA was 86.8.

[0094] Example 10

[0095] The only difference between this embodiment and embodiment 1 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0096] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0097] Medium-grained WC powder, Co powder, NbScN powder and NbC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% are mixed in a mass ratio of 0.52:0.28:0.1:0.1, and then 2 wt% of polyethylene glycol is added to the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg, the ball-to-material ratio of the ball milling is 4:1, the milling is carried out for 28 hours, and the mixture is spray-dried and granulated to obtain a medium-grained mixture;

[0098] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0099] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.6 μm, the average grain size of the super-coarse-grained WC was 6.6 μm, the bending strength was 2660 MPa, and the Rockwell hardness HRA was 86.4.

[0100] Embodiment 11

[0101] The only difference between this embodiment and embodiment 8 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0102] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0103] Medium-grained WC powder, Co powder and NbScN powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% are mixed in a mass ratio of 0.58:0.28:0.14, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg, the ball-to-material ratio of the milling is 4:1, the milling is carried out for 28 hours, and the mixture is spray-dried and granulated to obtain a medium-grained mixture.

[0104] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0105] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.8 μm, the average grain size of the super-coarse-grained WC was 6.5 μm, the bending strength was 2610 MPa, and the Rockwell hardness HRA was 86.6.

[0106] Example 12

[0107] The only difference between this embodiment and embodiment 8 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0108] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0109] Medium-grained WC powder, Co powder and NbC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% are mixed in a mass ratio of 0.58:0.28:0.14, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg, the ball-to-material ratio of the milling is 4:1, the milling is carried out for 28 hours, and the mixture is spray-dried and granulated to obtain a medium-grained mixture.

[0110] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0111] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.8 μm, the average grain size of the super-coarse-grained WC was 6.4 μm, the bending strength was 2650 MPa, and the Rockwell hardness HRA was 87.0.

[0112] Embodiment 13

[0113] The only difference between this embodiment and embodiment 8 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0114] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0115] NbScN powder, anhydrous ethanol and diethanolamine were put into a ball mill at a mass ratio of 1:0.2:0.001, the ball-to-material ratio was 1:1, ball milled for 3 hours, and vacuum dried to obtain modified NbScN powder; NbC powder, anhydrous ethanol and diethanolamine were put into a ball mill at a mass ratio of 1:0.2:0.001, the ball-to-material ratio was 1:1, ball milled for 4 hours, and vacuum dried to obtain modified NbC powder;

[0116] Medium-grained WC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% and Co powder, modified NbScN powder and modified NbC powder are mixed in a mass ratio of 0.58:0.28:0.06:0.08, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, and the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg. The ball-to-material ratio of the ball milling is 4:1. The mixture is milled for 28 hours and spray-dried to obtain a medium-grained mixture.

[0117] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0118] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.6 μm, the average grain size of the super-coarse-grained WC was 6.5 μm, the bending strength was 2700 MPa, and the Rockwell hardness HRA was 87.3.

[0119] Embodiment 14

[0120] The only difference between this embodiment and embodiment 11 is that the preparation method of WC-Co cemented carbide for mining is as follows:

[0121] Ultra-coarse particle WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder were mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol was added to the total weight of the ingredients, and wet-milled in a rolling ball mill, the milling medium was anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients was 200 ml / kg, and the ball-to-material ratio of ball milling was 3.5:1; ball milling was performed for 18 hours, and spray drying and granulation were performed to obtain an ultra-coarse particle mixture;

[0122] NbScN powder, anhydrous ethanol and diethanolamine were put into a ball mill at a mass ratio of 1:0.2:0.003, the ball-to-material ratio was 1:1, ball milled for 3 hours, and vacuum dried to obtain modified NbScN powder; NbC powder, anhydrous ethanol and diethanolamine were put into a ball mill at a mass ratio of 1:0.2:0.005, the ball-to-material ratio was 1:1, ball milled for 4 hours, and vacuum dried to obtain modified NbC powder;

[0123] Medium-grained WC powder with a Fess particle size of 5.0 μm and a carbon content of 6.15 wt% and Co powder, modified NbScN powder and modified NbC powder are mixed in a mass ratio of 0.58:0.28:0.06:0.08, and polyethylene glycol is added in an amount of 2 wt% of the total weight of the ingredients, and the mixture is wet-milled in a rolling ball mill. The milling medium is anhydrous ethanol, and the liquid-solid ratio of anhydrous ethanol to solid ingredients is 260 ml / kg. The ball-to-material ratio of the ball milling is 4:1. The mixture is milled for 28 hours and spray-dried to obtain a medium-grained mixture.

[0124] The ultra-coarse particle mixture and the medium particle mixture are mixed in a double cone mixer at a mass ratio of 9:1 for 80 minutes, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen removal of polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low pressure furnace at a sintering temperature of 1450°C to obtain WC-Co cemented carbide for mining.

[0125] The WC-Co cemented carbide for mining produced in this embodiment was tested, and it was found that the average grain size of the medium-grained WC of the WC-Co cemented carbide for mining in this embodiment was 1.5 μm, the average grain size of the super-coarse-grained WC was 6.5 μm, the bending strength was 2720 MPa, and the Rockwell hardness HRA was 87.4.

[0126] Comparative Example

[0127] The difference between this comparative example and Example 1 is that the WC-Co cemented carbide for mining is prepared by the following method:

[0128] Ultra-coarse WC powder with a Fess particle size of 15 μm and a carbon content of 6.145 wt% and Co powder are mixed in a mass ratio of 0.8:0.2, and then 2 wt% of polyethylene glycol is added to the total weight of the ingredients. The mixture is wet-milled in a rolling ball mill, the ball milling medium is anhydrous ethanol, the liquid-solid ratio of anhydrous ethanol to solid ingredients is 200 ml / Kg, and the ball-to-material ratio of ball milling is 3.5:1; after ball milling for 18 hours, the mixture is spray-dried and granulated, and then molded at 120 MPa. The pressed green body is placed in a dewaxing furnace for positive pressure hydrogen to remove polyethylene glycol and pre-sintered at 1400°C, and then sintered in a low-pressure furnace at a sintering temperature of 1450°C to obtain a WC-Co cemented carbide for mining.

[0129] The WC-Co cemented carbide for mining produced in this comparative example was tested, and it was found that the average grain size of the coarse grains WC of the WC-Co cemented carbide for mining in this comparative example was 11.5 μm, the bending strength was 2780 MPa, and the Rockwell hardness HRA was 80.6.

[0130] It can be seen from Examples 1-14 that, with reference to the formula and method disclosed in this application, the comprehensive performance of cemented carbide is greatly improved, the hardness and bending strength are relatively excellent, the wear resistance is good, the toughness is high, and the application requirements of cemented carbide for mining are met.

[0131] It can be seen from Examples 1-3 and the comparative example that the hardness and toughness of WC-Co cemented carbide are improved by matching medium-grained WC with ultra-coarse-grained WC, and the batch ratio of the ultra-coarse-grained mixture to the medium-grained mixture has a certain influence on the comprehensive performance of the cemented carbide. When the batch ratio is 9:1, the comprehensive performance of the cemented carbide is the best.

[0132] It can be seen from Example 1 and Examples 6-12 that by adding NbScN and NbC simultaneously, the two cooperate with each other to further improve the hardness and toughness of the cemented carbide, and the alloy performance reaches the best when 0.6wt% NbScN and 0.8wt% NbC are added.

[0133] In combination with Example 8, Example 13 and Example 14, it can be seen that the hardness and toughness of the cemented carbide are further improved by surface modification of NbScN powder and NbC powder. This may be because the surface coating modification of diethanolamine improves the uniformity of dispersion of NbScN powder and NbC powder, and further promotes the interface segregation and solid solution strengthening of NbScN powder and NbC powder.

[0134] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A WC-Co cemented carbide for mining, characterized in that: The invention comprises 15-30% Co, 0-1.5% NbScN, 0-1.5% NbC in a mass ratio, and the balance is a hard phase WC; The hard phase WC includes ultra-coarse grain WC with an average grain size of 6.0-9.0 μm and medium grain WC with an average grain size of 1.0-3.0 μm.

2. The WC-Co cemented carbide for mining according to claim 1, characterized in that: The cemented carbide comprises 0.5-1.0 mass percent of NbScN and 0.5-1.0 mass percent of NbC.

3. A method for preparing WC-Co cemented carbide for mining as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: According to the proportion, ultra-coarse particle WC powder and Co powder are mixed and prepared, and then 1.5-2.5% of the total weight of the ingredients is added to the molding agent, mixed and wet-milled for 14-20 hours, and then spray-dried and granulated to obtain an ultra-coarse particle mixture; the ultra-coarse particle WC powder has a Fess particle size of 13-20 μm; According to the proportion, medium-grained WC powder, Co powder, NbScN alloy powder and NbC alloy powder are mixed and prepared, and then a molding agent of 1.5-2.5% of the total weight of the ingredients is added, mixed and wet-milled for 20-30 hours, and then granulated by spray drying to obtain a medium-grained mixture; the Fess particle size of the medium-grained WC powder is 2-8 μm; The ultra-coarse particle mixture and the medium particle mixture are mixed and batched at a mass ratio of (85:15)-(95:5) for 40-80 minutes, pressed into shape, vacuum sintered to remove the molding agent, and then low-pressure hot isostatic pressing sintered at 1420-1450°C to obtain WC-Co cemented carbide for mining.

4. The method for preparing WC-Co cemented carbide for mining according to claim 3, characterized in that: The mass ratio of the super-coarse particle mixture and the medium particle mixture in a batch is 9:

1.

5. The method for preparing WC-Co cemented carbide for mining according to claim 3, characterized in that: The molding agent is polyethylene glycol.

6. The method for preparing WC-Co cemented carbide for mining according to claim 5, characterized in that: The NbScN alloy powder and the NbC alloy powder need to be surface modified by an alcoholamine compound. The surface modification method is: NbScN powder and / or NbC powder, anhydrous ethanol and diethanolamine are mixed in a mass ratio of 1: (0.1-0.2): (0.001-0.005) and ball-milled for 2-6 hours, and vacuum dried.

7. The method for preparing WC-Co cemented carbide for mining according to claim 3, characterized in that: In the preparation step of the ultra-coarse particle mixture, the wet grinding medium is anhydrous ethanol, the liquid-solid ratio is 180-230 ml / kg, and the ball-to-material ratio of wet grinding is 3:1-4:

1.

8. The method for preparing WC-Co cemented carbide for mining according to claim 3, characterized in that: In the step of preparing the medium-particle mixture, the wet grinding medium is anhydrous ethanol, the liquid-solid ratio is 200-300 ml / kg, and the ball-to-material ratio of wet grinding is 3.5:1-4.5:

1.

9. The method for preparing WC-Co cemented carbide for mining according to claim 3, characterized in that: The batching step is carried out in a double cone mixer or a Y-type mixer.

10. The method for preparing WC-Co cemented carbide for mining according to claim 3, characterized in that: The pressing step is performed by pressing the product using a molding method.

Citation Information

Patent Citations

  • Extra-coarse crystal grain carbide alloy material used for cutting pick or road excavation teeth, and its preparation method

    CN102220532A

  • Preparation method for super coarse crystal WC-Co hard alloy

    CN102808096A

  • Toughened hard alloy and preparation method thereof

    CN103882275A

  • Preparing method for nanometer toughening ultra-fine grain WC-Co cemented carbide

    CN107475548A

  • Hard alloy and preparation method thereof

    CN108118230A